Corporate disputes around the creation of wine geographical indications in Mendoza, Argentina - Larsimont, Robin; Martín, Facundo (Universidad Pedagógica y Tecnológica de Colombia, 2024)
The current corporate and neoliberal agri-food regime is actively reconfiguring the global geography of winemaking as we have known it up to now. Growing international competition is exacerbating regional strategies for distinguishing products and their patrimonialization mechanisms. This, evidenced by the proliferation of standardization and delimitation of production zones. Beyond the intercontinental quarrels that have arisen in the past, conflicts and tensions between scales are revealed, rapidly and fragilely intertwining actors and territories in the conformation of winegrowing places that need delimitation and institutionally recognized. In this paper we analyse the disputes over the definition of the Geographical Indication of Paraje Altamira in the oasis of the Uco Valley in Mendoza, Argentina in order to unravel the legitimization strategies deployed by business, scientific and state actors, and the power relations established between them in the framework of corporate wine territorialization. The analysis of this case study will allow us to critically assess the emergence of other similar initiatives that gave rise to a complex and hierarchical production of scales.